(untitled) (IJM: Journal of Multidisiplinary, 2024)
Teaching simulation is an educational training method aimed at enhancing teaching and educational skills by allowing teachers to interact directly with students in a small-scale and controlled environment. This study aims to explore the impact of teaching simulation on the mastery of effective teaching techniques in Civic Education learning at Elementary Schools. The research method employed is logical phenomenon with data collection through interviews. The results indicate that teaching simulation effectively enhances teachers' abilities to implement more effective teaching techniques. Active interaction between teachers and students in teaching simulations also improves students' understanding of the subject matter. Additionally, the study identifies that teaching simulation can enhance the quality of Civic Education learning by encouraging students to think critically and actively participate in democratic processes. Therefore, teaching simulation emerges as a crucial strategy for improving education at the elementary level, focusing on developing teaching skills and fostering student engagement in active learning.